2016
DOI: 10.1103/physrevlett.116.017204
|View full text |Cite
|
Sign up to set email alerts
|

Heat Transport in Spin Chains with Weak Spin-Phonon Coupling

Abstract: The heat transport in a system of S = 1/2 large-J Heisenberg spin chains, describing closely Sr2CuO3 and SrCuO2 cuprates, is studied theoretically at T J by considering interactions of the bosonized spin excitations with optical phonons and defects. Treating rigorously the multiboson processes, we derive a microscopic spin-phonon scattering rate that adheres to an intuitive picture of phonons acting as thermally populated defects for the fast spin excitations. The meanfree path of the latter exhibits a distinc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…30b is the fact that at T 100 K the mean free path becomes significantly smaller than that of both the 2-leg ladder and of the plane compounds. Since the temperature-induced reduction of l mag of the spin chain materials has clearly been assigned to spinonphonon scattering [39,40,64], this observation seems to imply that the spinon heat transport of the S = 1/2 Heisenberg chain is much more prone to scattering of phonons than the two-leg Heisenberg ladder and the 2D-HAF counterparts. It remains to be clarified to what extent this notion is related to the integrability of the Heisenberg chain model, whose ballistic transport properties potentially could exhibit a particular sensitivity to distortions such as those induced by the phonons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…30b is the fact that at T 100 K the mean free path becomes significantly smaller than that of both the 2-leg ladder and of the plane compounds. Since the temperature-induced reduction of l mag of the spin chain materials has clearly been assigned to spinonphonon scattering [39,40,64], this observation seems to imply that the spinon heat transport of the S = 1/2 Heisenberg chain is much more prone to scattering of phonons than the two-leg Heisenberg ladder and the 2D-HAF counterparts. It remains to be clarified to what extent this notion is related to the integrability of the Heisenberg chain model, whose ballistic transport properties potentially could exhibit a particular sensitivity to distortions such as those induced by the phonons.…”
Section: Resultsmentioning
confidence: 99%
“…However at lower temperature, the agreement between the experimental results and the theoretical l sp becomes less satisfactory (see [40] for details). Very recently, Chernyshev and Rozhkov reanalyzed the experimental data of Hlubek et al for both SrCuO 2 and Sr 2 CuO 3 with an alternative theoretical model which specifies l sp including realistic numerical values for the spin-phonon interaction [64]. Also in this case, the analysis relies for both compounds on just two types of scattering processes, viz.…”
Section: Ballistic Spinon Heat Transport In Sr 2 Cuomentioning
confidence: 99%
“…Working with ballistic QWs, in the following we will see that the CCT and the HCT are only affected by the scattering processes at the central island. While our approach is effective in working out the zero-temperature, fixed point properties of the junction, in general other effects, which we do not consider here, such as coupling with phonons, may become effective in determining the finite-temperature transport properties of our system [68] (see, e.g., [38 and 69] for a comprehensive discussion of several possible physical mechanisms affecting the thermal transport properties of an electronic system). In Fig.…”
Section: A Electric and Thermal Conductancementioning
confidence: 99%
“…58 Previous studies of thermal transport in insulating magnetic materials indicated that the magnetic and thermal contributions to the thermal conductivity can be comparable. [59][60][61][62][63][64] Our main result in this work is to show that the spatially anisotropic magnetic states that can arise from strong spin-orbit coupling can dramatically affect the thermal transport, or have a rather small effect depending on the relative size of magnon and phonon thermal conductivities. In some cases, the thermal transport may help identify the symmetries of the magnetically ordered state if other measurements are difficult or problematic.…”
Section: Introductionmentioning
confidence: 99%